2022
DOI: 10.3389/fnagi.2021.755926
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Cognitive Frailty: A Systematic Review and Meta-Analysis

Abstract: ObjectiveCurrently, the prevalence of CF (Cognitive Frailty) is not very clear, and the relationship between CF and its associated risk factors has not been accurately evaluated. Therefore, it is necessary to conduct a systematic review and meta-analysis further to understand CF's prevalence and associated factors.MethodsEmbase, PubMed, Web of Science, Ovid, and Cochrane were systematically searched for articles exploring the prevalence of CF, the deadline of searching date was up to March 2021. For the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 59 publications
7
47
1
Order By: Relevance
“…Thus, subjective satisfaction with relationships including friends, community may be more influential on the health outcomes of older adults than the structural aspects of social relationships, which is supported by previous studies ( 39 , 40 ). Participation in social activities and social contacts was most consistently associated with preservation of global cognitive function ( 13 , 41 43 ) and prevention or slowing down of the process of physical frailty ( 44 ) across all study types. The theory of “use it or lose it” ( 45 ) suggests that the brain can be considered a muscle; thus, social activities may stimulate the brain and contribute to the preservation of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, subjective satisfaction with relationships including friends, community may be more influential on the health outcomes of older adults than the structural aspects of social relationships, which is supported by previous studies ( 39 , 40 ). Participation in social activities and social contacts was most consistently associated with preservation of global cognitive function ( 13 , 41 43 ) and prevention or slowing down of the process of physical frailty ( 44 ) across all study types. The theory of “use it or lose it” ( 45 ) suggests that the brain can be considered a muscle; thus, social activities may stimulate the brain and contribute to the preservation of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, no research has tested the mediating role of loneliness between depression and cognitive frailty using the mediating model. Previous studies showed that depression is associated with cognitive frailty [ 10 , 39 ], but the potential mechanism has not been revealed. Our results demonstrated that older adults with depressive symptoms have a stronger sense of loneliness, which is related to their greater possibility of cognitive frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty has been described as a multidimensional clinical gerontological syndrome ( 6 , 7 ). A cumulative decline of multiple physiological systems leads to reduced energy reserves, increased susceptibility to stressors, and dysregulated physiological system dynamic balance ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The former is indicated by mild cognitive impairment (MCI) (CDR = 0.5), and the latter by a pre-MCI subjective cognitive decline (SCD) (CDR = 0) and positive biomarkers of neurodegeneration ( 17 ). A meta-analysis showed that the estimated prevalence of cognitive frailty was 6% in older people community-dwelling ( 7 ). Recognition of associations between predictors as mild cognitive impairment and frailty alone and combined, and multiple adverse health outcomes, could not only inform treatment decisions and goals of care, but also provide predictors for early identification and intervention among the increasing old populations to reduce the occurrence of adverse health outcomes ( 18 ).…”
Section: Introductionmentioning
confidence: 99%